Modos de fazer na socioeducação: perspectivas de profissionais do meio aberto - Oliveira, Izabela dos Santos de (2021)
This research aims to identify and analyze the practices of professionals who work or have already worked in Social and Educational Measures Services in Liberty with adolescents and young people in the light of a critical and autonomy-producing perspective. More specifically, we seek to contextualize the practices of these professionals based on regulations and literature in the area, as well as identify and characterize ways of thinking and doing socio-education by professionals in the open environment. For this, we rely on the literature review on the subject, and, more specifically, on works that discuss professional practices and work methodologies in socio-educational measures services. We interviewed four professionals who work and/or have worked in socio-educational measures services in an open environment to learn about their professional experiences and their ways of doing social education. We used content analysis to analyze the interviews and the following thematic axes were identified: training itineraries; conceptions of socio-education, the diversity of socio-educational practices, and work processes. It was possible to see that professionals forge critical practices and invent new paths in this action in socio-education, based on political and autonomy-producing practices for adolescents